Identitas Moral: Rekonstruksi Identitas Keindonesiaan pada Era Globalisasi Budaya - Hapsoro, Leonardus Pandu (Masyarakat: Jurnal Sosiologi, 2015)
This article discusses about the process of identity reconstruction of actor in KISS community in the era of cultural globalization. Using a qualitative method and Zygmunt Bauman’s concept of liquid modernity and moral agency as framework analysis, this study shows how the construction of moral identity process begins with the actor disquite over the state of traditional culture in globalization era. The author argues that the expression of the identity of actor through this social movement will create the role of cultural diversity in the era of cultural globalization and liquid modernity. The author wants to move away from an agentless view of globalization process by viewing at the dynamics of the agency. Through agents and the form of moral agency, the author also argues that in the process and impact of globalization, people are not retained on the condition of “is” or structural pressure, but their is an optimism to see any hope on the condition that “should” or a better from an identity consciousness and morality